The ugly princess and the wise fool - Gray, Margaret, 1969-; Cecil, Randy (New York : Henry Holt, 2002)
When plain-looking Princess Rose longs for the beauty to snare handsome Prince Parsley, and the wise fool Jasper longs to restore wisdom to the kingdom, they end up working together and find they must face the Godmother Board of Trustees.
Keywords: Fairy tales; Princesses -- Fiction; Personal appearance -- Fiction; Intellect -- Fiction; Magic -- Fiction; Humorous fiction